The need for regulating animal testing: a comparative study between Malaysia and United Kingdom / Nur Farhana Abdul Latiff … [et al.] - Abdul Latiff, Nur Farhana; Hussein, Athari Faris Ammerry; Ishak, Zairan; Khalip, Abdul Hakim Hissobri (2011)
This research covers law relating to legal protection of animals welfare precisely on animal testing in Malaysia with comparison to United Kingdom. The aim is to embark on analyzing the comprehensiveness of the Animals Act 1953 with regards to animal testing in comparison to the law in United Kingdom, Animals (Scientific Procedures) Act 1986. It is also to emphasize on the importance of codifying the code of practice in statutory form pertaining to animal testing in Malaysia. This study shall look at the loopholes under the Animals Act 1953 in Malaysia regarding animal testing in comparison with the law that being applied in United Kingdom, Animals (Scientific Procedures) Act 1986. The significance of literature review in this study are to gain the relevant information and opinion from the experts regarding law on animal testing in Malaysia and United Kingdom, to collect data in detail, to discover the loopholes in Animals Act 1953 and to provide the appropriate solutions and recommendations pertaining the issue in this research paper.